KEARIFAN LOKAL PADA CERITA RAKYAT DALAM BUKU TEKS BAHASA INDONESIA KELAS X SMA - Zhafira Usmadilla; Usman; Aswati Asri (STKIP Subang, 2025)
This study is a qualitative descriptive study that aims to describe the values ​​of local wisdom contained in folklore in Indonesian language textbooks for grade X of high school. The data of this study are in the form of words or sentences containing local wisdom values ​​contained in folklore texts while the data source of the study is the Indonesian language textbook for grade X of high school. The data collection techniques used are reading techniques, note-taking techniques. The results of the study show that: The focus of this study is how are the values ​​of local wisdom contained in folklore in Indonesian language textbooks for grade X of high school. The values ​​of local wisdom are politeness, honesty, social solidarity, harmony, conflict resolution, commitment, positive thinking, gratitude, hard work, caring for the environment, discipline, education, health, mutual cooperation, gender management, cultural creativity, and responsibility.